Protein Profile and Hematological Parameters of Mice post Injected with Irradiated Plasmodium berghei - Imam Rosadi; Mukh Syaifudin; Dewi Elfidasari (Biosaintifika: Journal of Biology & Biology Education, 2016)
Indonesia had a high number of malaria cases where the treatments are only perceived by 10% of patients in health facilities. The resistance of Plasmodium sp. to drugs causes the difficulty of controlling malaria. The use of irradiation to produce malaria vaccine material is being explored until nowadays. In previously study that dose rate of gamma irradiation delivered to parasite was at the low dose rate (380 Gy/hour) which produced several doses that not be able to attenuate the parasite. This research aimed to increase dose rate (740 Gy/hour) and to determine the dose irradiation effect of 150-250 Gy to the protein profile, erythrocyte and leukocyte numbers in mouse blood infected by P. berghei erythrocytic stage. Results showed that there was an influence of dose rate of 740 Gy/hour for doses of  150-250 Gy in treated mice and no difference in erythrocyte, leucocyte and body weight with negative control. Dose of 150 Gy was the optimal dose to attenuate parasites, whereas doses more than 150 Gy effectively killed the parasites. The changes of protein profile marked by the appearance of higher number of bands at molecular weight of 30-37 kDa that predicted as merozoite surface protein of  P. berghei and/or antibodies elicited in mouse.How to CiteRosadi, I., Syaifudin, M., Elfidasari, D. (2016). Protein Profile and Hematological Parameters of Mice post Injected with Irradiated Plasmodium berghei. Biosaintifika: Journal of Biology Biology Education, 8(2), 155-164